Development of Dewatering Textile Materials Incorporating Slit-Pore Geometries - Westhaver, Kurt (My University, 2018)
The treatment of municipal, industrial and agricultural wastewater produces a semi-liquid mixture known as sludge. The costs associated with pumping, transporting, treating, storing, and disposing of sludge are significant. Therefore, sludge dewatering techniques are employed to increase the solids content of the material by separating the solid and liquid components, thus reducing the overall volume requiring further handling. Non-mechanical dewatering methods require large areas of land and favorable climatic conditions, while mechanical dewatering technologies require significant capital investment and ongoing operation and maintenance by highly trained personnel. Due to these shortcomings, the conventional methods of sludge dewatering are not applicable to scenarios where: the quantity of sludge is small, there is limited budget, there are land restrictions, or dewatering is performed seasonally. An alternative approach that has recently attracted considerable attention is the use of dewatering fabrics; specially engineered textiles supplied in the form of very large bags into which the sludge is pumped. The concept itself is simple, pressure inside the bag pushes the free water through the fabric while the solid material is retained within. Unfortunately, these products have exhibited poor dewatering performance for certain feed materials. In this work, a series of ‘next-generation’ engineered dewatering fabrics featuring elongated ‘slit’ pores were produced using laser cutting techniques. A comprehensive analysis of the effect of the filter properties on dewatering performance was performed using sludge sourced from two different operations: municipal wastewater treatment and precious metal mining.
Keywords: Geotextile; Dewatering; Sludge; Wastewater